2005
DOI: 10.1152/ajplung.00040.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase stimulatesMUC1gene expression through increased Sp1 binding to theMUC1promoter

Abstract: We previously reported MUC1 was a cell surface receptor for Pseudomonas aeruginosa, and binding of bacteria to cells was significantly reduced by pretreatment with neutrophil elastase (NE) (Lillehoj EP, Hyun SW, Kim BT, Zhang XG, Lee DI, Rowland S, and Kim KC. Am J Physiol Lung Cell Mol Physiol 280: L181-L187, 2001). The current study was conducted to ascertain NE effects on MUC1 gene transcription, and MUC1 protein synthesis and degradation. A549 human lung carcinoma cells treated with NE exhibited significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 62 publications
4
47
0
1
Order By: Relevance
“…The mucus with bacterial burden will be cleared from the mucosal surface by cilia beating (26). Under inflammatory environment, the sputum EC fragments came from a neutrophil elastase mediated degradation of EC MUC1 on the surface of airway epithelial cells (11). However, excessive mucus production will contribute to airway blockage and lung functions decline, a situation consistent with positive correlation between sputum MUC1 EC fragment level and obstruction (determined by FEV 1 /FVC value reduction) revealed by linear regression analysis (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucus with bacterial burden will be cleared from the mucosal surface by cilia beating (26). Under inflammatory environment, the sputum EC fragments came from a neutrophil elastase mediated degradation of EC MUC1 on the surface of airway epithelial cells (11). However, excessive mucus production will contribute to airway blockage and lung functions decline, a situation consistent with positive correlation between sputum MUC1 EC fragment level and obstruction (determined by FEV 1 /FVC value reduction) revealed by linear regression analysis (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…An indispensable antiinflammatory role of Muc1 has been found in the airway during Pseudomonas aeruginosa and respiratory syncytial virus infection (8,9). Muc1 levels in bronchoalveolar lavage (BAL) fluid were increased during the acute phase of lung inflammation and positively correlated with TNF-α level increase (8,10) and neutrophil elastase levels upregulation (11). Chronic airway inflammation is one of characteristics of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that NE upregulates a cytoplasmic oxidoreductase, NADPH quinone oxidoreductase 1 that is required for NE-induced lipid peroxidation and for NE-regulated MUC5AC mRNA expression . NE also upregulates two membrane-associated mucins, MUC4 (Fischer, 2003) and MUC1 (Kuwahara et al, 2005), in airway epithelial cells. MUC1 and MUC4 regulate intracellular signaling via the ErbB family of receptor tyrosine kinases in cancer cells (Hollingsworth and Swanson, 2004) and may have similar functions in the lung.…”
Section: Neutrophil Elastase and Mucins Mucus Secretion And Mucocilmentioning
confidence: 98%
“…Signaling through these pathways may affect the apoptotic state of the cell, which may explain the greater expression of MUC1 in neoplastic cells (126). MUC1's expression in airway epithelial cells can be induced by NE and CpG DNA from bacteria (127,128). Otherwise, it is regulated by inflammatory mediators in noncancerous airway cells.…”
Section: Regulation Of Other Mucin Genes In the Lungsmentioning
confidence: 99%